ANALISIS PENGENDALIAN INTERN ATAS SISTEM PENGGAJIAN DAN PENGUPAHAN PADA CV. CITRA SARI MAKASSAR - Silvister Saman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aims to determine the elements of internal control in the payroll system and the company CV.Citra pengupahaan Sari Makassar. While the methods of analysis used is descriptive method of research trying to describe or illustrate a phenomenon, an event occurrence that occurred in the present and focused on solving the problems as they are at the time of research conducted. The results of this study is the organizational structure CV. Citra Sari Makassar illustrates a clear separation of functions between superiors and subordinates as well as the duties and responsibilities pemabagian good to each employee,but there are still kerangkapan duty on the part of the administrative staff do not meet the standards of the elements of internal control sufficient memadai. Fungsi- related functions in the payroll system and employee pengupahaan CV. Citra Sari Makassar had been carrying out their responsibilities well but theadministration still serves as timekeeper present, maker of payroll and also carry out the payment of wages karyawan.Praktik healthy at CV. Citra Sari Makassar can be good, but there is a shortage at the time of recording the time that the employee confirm their attendance, there is no special section that oversees theprocess of recording time.